Stresses and deformations in flexible layered pavement systems subjected to dynamic loads - Brown, S.F. (1967)
Many of the proposed rational design methods for flexible pavements are concerned with the stresses and strains which occur in the various layers of the structure. The purpose of the work reported is to investigate, in the laboratory, the complete stress and strain distributions set up in the different layers under dynamic loads.